Brassinosteroids Positively Regulate Plant Immunity via BRI1-EMS-SUPPRESSOR 1-Mediated GLUCAN SYNTHASE-LIKE 8 Transcription - Xiong, Jiawei; Wan, Xiaoping; Ran, Maolin; Xu, Xiumei; Chen, Lezhang; Yang, Feng (Frontiers in Plant Science, 2022)
Plant hormone brassinosteroids (BRs) play key roles in plant adaptation to biotic stresses, including various pathogens infection. As a core factor in BRs signaling, the transcription factor BRI1-EMS-SUPPRESSOR1 (BES1) activates BR responses via regulating target genes expression. However, the molecular mechanism of BRs in regulating plant immunity is unclear and the key component is not identified. In this study, we found BRs biosynthesis and signaling transduction are essential for plant resistance to pathogen infection, BR biosynthesis or BR signaling deficient mutants displayed susceptibility to Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) infection (including more serious symptoms and more PSII photochemistry damage). We identified a callose synthase gene GLUCAN SYNTHASE-LIKE 8 (GSL8) as a direct target of BES1 and its expression is induced by BRs/BES1. Meanwhile BRs induced callose accumulation after Pst DC3000 infection. Moreover, BES1 gain of function mutant bes1-D showed promoted Pst DC3000 resistance. GSL8 T-DNA insertion mutant gsl8-1 was susceptible to DC3000, while brassinolide (BL)-treatment partially rescued gsl8-1 susceptible phenotypes. Our study suggests that BRs-induced pathogen resistance partly depend on BR-induced BES1-GSL8 cascade to mediate callose accumulation.